2015
DOI: 10.3389/fmicb.2015.00279
|View full text |Cite
|
Sign up to set email alerts
|

CRH promotes S. pneumoniae growth in vitro and increases lung carriage in mice

Abstract: Streptococcus pneumoniae (S. pneumoniae), a commensal across the nasal passages, is responsible for the majority of infectious pneumonia cases worldwide. Previous studies have shown that hormonal factors may be influential in regulating S. pneumoniae’s transition from a non-pathogen to a pathogenic state. The current study investigated the effects of corticotropin-releasing hormone (CRH), a peptide hormone involved in stress, on the pathogenicity of S. pneumoniae. Mice were infected with CRH-treated S. pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Little is known however, regarding a bacterial species' response to CRH and other neuroendocrine factors as determinants of its virulence and pathogenicity. In previous studies, we were the first to demonstrate, to our knowledge, that CRH could directly impact S. pneumoniae's growth and in vivo pathogenesis (Ndjom and Jones, 2015 ). The results of the current study indicate that CRH potentiates morphological, genetic and functional properties vital to S. pneumoniae's virulence.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Little is known however, regarding a bacterial species' response to CRH and other neuroendocrine factors as determinants of its virulence and pathogenicity. In previous studies, we were the first to demonstrate, to our knowledge, that CRH could directly impact S. pneumoniae's growth and in vivo pathogenesis (Ndjom and Jones, 2015 ). The results of the current study indicate that CRH potentiates morphological, genetic and functional properties vital to S. pneumoniae's virulence.…”
Section: Discussionmentioning
confidence: 98%
“…We also found that pre-exposing S. pneumoniae to CRH increased bacterial counts in the lung. Furthermore, direct exposure to CRH resulted in increased bacterial growth, and Pneumococcal-associated virulence factor A (pavA) gene expression (Ndjom and Jones, 2015 ). Collectively these results suggest a possible correlation between a bacterial pathogen's response to stress hormones (e.g., glucocorticoids) and the risk for developing sepsis and septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…Proteolytic degradation of neuropeptides by microbial proteases, however, seems to be a different and more likely matter. The findings that various bacteria such as P. aeruginosa , E. faecalis , Proteus mirabilis , S. enterica , S. pyogenes , Burkholderia cenocepacia , Vibrio cholera and pathogenic yeasts such as C. albicans can cleave pivotal antimicrobial peptides including LL-37 appear to support this notion [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 …”
Section: Have Neuropeptides Met Their Expectations As Anti-infectimentioning
confidence: 99%
“…Interestingly, neurochemicals secreted during stressful events can potentially influence the composition of the respiratory tract microbiota, as these neurochemicals can interact with bacterial pathogens, modifying their growth and expression of virulence-related factors ( Lyte, 2014 ). Corticotropin-releasing hormone, a peptide hormone involved in the stress response, enhanced growth and virulence of the human respiratory pathogen Streptococcus pneumoniae , and is thought to be involved in its transition from a non-pathogenic to a pathogenic state ( Ndjom and Jones, 2015 ). In cattle, the abundance of M. haemolytica was markedly increased in recently weaned calves that were transported > 1,600 km ( Frank and Smith, 1983 ), perhaps also suggesting that the microbiota of the bovine respiratory tract respond to stress factors.…”
Section: Introductionmentioning
confidence: 99%